Current state and development prospects of Uzbekistan’s electric power industry - Kakhramon R. Allaev; Ikromjon U. Rakhmonov; Umid M. Mamadaminov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2025)
Relevance: this article analyzes the current state and development prospects of Uzbekistan's electric power industry within the context of sustainable economic growth and improved quality of life for the population. It highlights that the country's installed power capacity reached 23.1 GW by 2024 and emphasizes the necessity to double electricity production by 2030 due to rising energy demand. The goal: to enhance the efficiency of Uzbekistan's electric power system by modernizing the energy sector through the integration of renewable energy sources (solar and wind energy), the development of nuclear power plants, and the attraction of foreign investments. Methods: analysis of the structure of energy generation and major energy resources (both conventional and renewable), assessment of the efficiency of market mechanisms, and evaluation of the effectiveness of foreign investments. Results: the article substantiates the potential for reducing natural gas consumption and improving the environmental situation through the construction of nuclear power plants. Additionally, it provides rationale for increasing the share of solar and wind energy in the country's energy balance to approximately 50% by the years 2030-2035. Keywords: electric power industry, sustainable development, renewable energy sources, nuclear energy, energy saving, investments, energy reforms.